Identification of Dark Pricing Patterns in Marketplaces: A Promotional Content Study - Helena Audrey Gunawan; Najwa Adinda Firmawati; Anna Triwijayati (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This research is motivated by the rapid growth of the digital economy in Indonesia, which is paradoxically accompanied by the rise of user interface manipulation tactics, or dark pricing patterns, in various marketplace applications. The main objective of this study is to identify unethical price manipulation patterns, such as hidden costs, sneak-into-basket, and false urgency in promotional content, and to analyze in depth their impact on consumer decision-making processes. The basic approach of this research uses exploratory descriptive qualitative methods. Data collection was conducted comprehensively through interface observations (interface audits) and in-depth literature reviews related to consumer behavior, which were then analyzed thematically based on the concepts of choice architecture and dual process theory. The analysis results show significant findings that dark pricing patterns have operated systematically to exploit impulsive cognitive processing to expedite transactions unreasonably. Crucial findings reveal that this practice triggers negative sentiment and is detrimental to consumers when non-transparent service fees appear at the final stage of payment. This study concludes that while this design manipulation tactic has proven highly effective in increasing short-term purchase conversion rates, it has a destructive impact by eroding consumer autonomy, triggering post-decision regret, and undermining the essential foundation of public trust. Consequently, specific legal regulatory reforms regarding comprehensive price transparency are needed, as well as the implementation of behavioral interventions in the form of postponement features within systems to protect digital consumers in Indonesia.